Information for contributors and readers for issue 1-2017 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Ministry of Education, Science and Technological Development of the Republic of Serbia classified the Military Technical Courier for the year 2014